Good Forest Governance: Sebuah Keniscayaan dalam Pengelolaan Sumberdaya Hutan Lestari - Bowo Dwi Siswoko (Fakultas Kehutanan Universitas Gadjah Mada, 2009)
Good Forest Governance: A Necessity in Sustainable Forest Resource ManagementForest resources development is one of natural resource management sectors implemented centrally during the period of New Order (Orde Baru). Forest resource management was executed exploitatively and centrally without considering local and regional aspirations, causing abandonment of local communities. Communities living near and in the forest were neglected and did not have any access to gain forest benefits appropriately. This has caused conflicts between state and communities upon forest resources utilization that to some extent has initiated forest resource degradation.Since the political reformation in 1998, along with more democratic and stronger civil society in Indonesia, good forest governance concept was believed as a strategy that is able to accommodate the dynamic and answer various problems in forest resource management. In this concept, state has to acknowledge its inadequacy in forest resource management. Government should share roles and authorities to other stakeholders in proportion to each capability. Government was forced to be able to accommodate and provide participatory space to the communities in every step of forest management activities. Additionally, ecological aspect has also to be the primary consideration in this strategy. By applying good forest governance concept that is always based on social and ecological aspects, it is expected that forest resource sustainability and community welfare improvement could be realized.